Factors associated with vulnerability and fragility in the elderly: a cross-sectional study - Caroline Ribeiro de Sousa; Janaína Fonseca Victor Coutinho; João Bastos Freire Neto; Rachel Gabriel Bastos Barbosa; Marília Braga Marques; Jamylle Lucas Diniz (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to assess factors associated with vulnerability and fragility in the elderly. Methods: crosssectional study with 384 elderly people in Fortaleza, Ceará. The Vulnerable Elders Survey and Clinical-Functional Vulnerability Index - 20 were used. Chi-square and Fisher's exact tests were used for associations. In the analysis of the combined influence of risk factors, the stepwise logistic regression and multinomial regression methods were adopted. Results: 251 (65.4%) non-vulnerable and 133 (34.6%) vulnerable elders. From the vulnerable elders analyzed, 42 (30.9%) are at high risk for frailty. Factors associated with vulnerability: age, gender, presence of comorbidities, hypertension, diabetes, osteoporosis and use of polypharmacy. There is a 30% increase in the chance of vulnerability for each additional drug. Physical activity reduces the chance of vulnerability by 60%. Factors associated with frailty: educational level; self-perception of health; comorbidities; polypharmacy. Conclusions: it is important to pay attention to the presence of arterial hypertension, osteoporosis, polypharmacy, and encourage the practice of physical activity.